Dobrowolne ubezpieczenia zdrowotne w Polsce - stan obecny i perspektywy rozwoju - Jackowska, Beata; Pobłocka, Agnieszka (Voluntary Health Insurance in Poland - Actual State and Perspectives of Development, 2006)
Health insurance protects people against the financial consequences of illness: medical care expenses and losses of earned income. Voluntary health insurance does not play a dominant role in funding health care in the European Union, however in Poland and other EU member states levels of private expenditure on health care increase and the benefits provided by the statutory health care system (particularly dental care and pharmaceuticals) are reduced. The aim of this work is to show the health insurance market in Poland and to discuss the current developments of voluntary health insurance.1. This work is structured as follows: 2. The characteristics of health insurance. 3. Health expenditure in Poland and in chosen countries. 4. The market for voluntary health insurance in Poland. 5. Trend of the health insurance market - proposals for Poland.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1108, s. 205-215